DETERMINASI FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Wida Ramadhan, Adelia Ari; Setiawati, Erma (ITB AAS Indonesia Surakarta, 2025)
This research aims to test and analyze the influence of capital structure, profitability, company size, dividend policy, company growth on company value. Some of the variables used in this research are capital structure, profitability, company size, dividend policy, company growth, and company value. The population in this study are manufacturing companies in basic and chemical industry sectors listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. The sampling technique is through purposive sampling. The number of samples used was 24 companies and the amount used was 96 data. The analytical methods used in this research are descriptive analysis methods, inductive analysis, classical assumption test analysis, and the adjusted coefficient of determination R2. The research results show that capital structure, company size, dividend policy and company growth have no effect on the condition of company value in manufacturing companies in basic and chemical industry sectors listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. Meanwhile, profitability influences the condition of company value, in manufacturing companies in basic and chemical industry sectors listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period.Keywords: capital structure, profitability, company size, dividend policy, company growth